2021
DOI: 10.21203/rs.3.rs-208751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interfacial Chemical Bond and Internal Electric Field Modulated Z-Scheme Vs-ZnIn2S4/MoSe2 Photocatalyst for Efficient Hydrogen Evolution

Abstract: Construction of Z-scheme heterostructure is of momentous significance for realizing efficient photocatalytic water splitting. However, the consciously modulate of Z-scheme charge transfer is still a great challenge. Herein, interfacial Mo-S bond and internal electric field modulated Z-Scheme heterostructure composed by sulfur vacancies-rich ZnIn2S4 (Vs-ZIS) and MoSe2 was rationally fabricated for efficient photocatalytic hydrogen evolution. Systematic investigations reveal that Mo-S bond and internal electric … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As shown in Figure 2h,i, the Zn 2p, In 3d, and S 2p peaks of ZIS-1 were in accord with the BDE data reported. 46 For the ZIS-3 and ZIS-6 samples, the S 2p peaks could be divided into two different types of peaks, which indicated that S 2− was in different chemical bonding environments, possibly ZnS and ZnIn 2 S 4 . 47 Furthermore, in samples ZIS-3 and ZIS-6, the BDE positions of the elements were negatively shifted with increasing the Zn content, which was attributed to the less electronegativity of Zn compared to ZIS-1.…”
Section: The Chemicals Included Znmentioning
confidence: 95%
“…As shown in Figure 2h,i, the Zn 2p, In 3d, and S 2p peaks of ZIS-1 were in accord with the BDE data reported. 46 For the ZIS-3 and ZIS-6 samples, the S 2p peaks could be divided into two different types of peaks, which indicated that S 2− was in different chemical bonding environments, possibly ZnS and ZnIn 2 S 4 . 47 Furthermore, in samples ZIS-3 and ZIS-6, the BDE positions of the elements were negatively shifted with increasing the Zn content, which was attributed to the less electronegativity of Zn compared to ZIS-1.…”
Section: The Chemicals Included Znmentioning
confidence: 95%
“…1. It is well known that precise control of the morphology of semiconductor photocatalysts plays an important role in improving their physical and chemical properties and the performance of photocatalytic systems (Xie et al, 2021;Xuehua Wang et al, 2021;Cheng et al, 2022;Mingming Liu et al, 2022;Wang et al, 2022;Xia Liu et al, 2022). The photocatalytic performance of ZnIn 2 S 4 photocatalyst can be significantly improved by morphological adjustment, which can be attributed to the following four factors: 1) the specific surface area of ZnIn 2 S 4 can be increased; 2) it promotes mass transfer and light capture; 3) it is beneficial to expose more active sites on the surface that can participate in redox reactions; 4) it shortens the migration distance and accelerates the migration speed of photogenerated carriers.…”
Section: Optimization Of Photocatalytic Hydrogen Evolution Performanc...mentioning
confidence: 99%